When Jack came back [videorecording (DVD)] - Moreno, Thor; Henriksen, Lance, 1940-; Wagner, Lindsay; Markoff, Mike (Dreamscape Media, 2023)
Jack, a down-on-his-luck actor, begrudgingly comes home after the death of his father only to find that his mom is in the grip of Alzheimer's disease.